Violência que cruza fronteiras: mapeando e categorizando violências que perpassam a realidade de pessoas refugiadas e solicitantes de refúgio LGBTQIA+ - Junqueira Neto, Antonio Teixeira (2024)
The 1951 United Nations Convention Relating to the Status of Refugees and its 1967 Protocol serve as international normative references concerning the protection of individuals persecuted and seeking refuge due to reasons such as race, religion, nationality, social group, or political opinions. However, this definition does not directly encompass certain vulnerable groups, such as individuals with diverse sexual orientations and/or gender identities, who are often subjected to discrimination and other forms of violence when forcibly displaced and seeking refuge as a means of protection. This research, therefore, aims to map and categorize, through documents and international jurisprudence, the forms of violence that constitute part of the experience of LGBTQIA+ refugees within the contexts of the Global System and Regional Human Rights Protection Systems. In this regard, the study seeks to explore the relationship between the state, normative frameworks, and individuals, with the aim of provoking and facilitating discussions concerning the realities faced by these individuals.